2021
DOI: 10.1007/s11136-020-02713-0
|View full text |Cite
|
Sign up to set email alerts
|

Examination of individual and multiple comorbid conditions and health-related quality of life in older cancer survivors

Abstract: Purpose Older cancer survivors (≥ 65 years at diagnosis) are at high-risk for multimorbidity (2 + comorbid conditions). However, few studies have utilized a generalizable sample of older cancer survivors to understand how individual comorbid conditions, as opposed to total comorbidity burden, are associated with health-related quality of life (HRQOL). We examined associations between HRQOL outcomes (pain, fatigue, physical function), individual comorbidities (cardiovascular disease [CVD], lung disease, diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
11
0
5
Order By: Relevance
“…Together with the findings of previous studies, the results of this study offer the insight that consideration of various potential risk and protective factors for health outcomes, including financial well-being, is a necessary step for identifying people with cancer who may need frequent monitoring and assistance with financial counseling and chronic disease management as they transition from treatment to survivorship. 4 This implication is important because many interventions to address financial toxicity focus on the direct and indirect costs of cancer and its treatment, which are usually delivered by oncology social workers and cancer-specific not-for-profit organizations. 41,42 First, financial navigation and counseling interventions continue to be developed in oncology, and it is important that such interventions also address financial concerns related to conditions other than cancer.…”
Section: Pathmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with the findings of previous studies, the results of this study offer the insight that consideration of various potential risk and protective factors for health outcomes, including financial well-being, is a necessary step for identifying people with cancer who may need frequent monitoring and assistance with financial counseling and chronic disease management as they transition from treatment to survivorship. 4 This implication is important because many interventions to address financial toxicity focus on the direct and indirect costs of cancer and its treatment, which are usually delivered by oncology social workers and cancer-specific not-for-profit organizations. 41,42 First, financial navigation and counseling interventions continue to be developed in oncology, and it is important that such interventions also address financial concerns related to conditions other than cancer.…”
Section: Pathmentioning
confidence: 99%
“…1,2 Recent studies have also demonstrated that multimorbidity has significant negative impacts on health-related quality of life (HRQoL), a multidimensional concept that takes into account an individual's physical, psychological, and social functioning over time. 3,4 These studies have shown that a cumulative multimorbidity burden is associated with low HRQoL, regardless of the chronic conditions involved. For instance, compared with older cancer survivors reporting only one comorbidity, those with two or more comorbid conditions reported worse pain, fatigue, and greater physical function limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследователи полагают, что знание специфического профиля сопутствующих заболеваний больного, перенесшего рак, позволяет получить представление о параметрах связанного со здоровьем качества жизни, которые могут быть нарушены в процессе противоопухолевого лечения, в то время как понимание общей тяжести сопутствующих патологий (независимо от конкретных состояний) проливает свет на общее качество жизни. Эта информация может быть использована при формировании программ комплексной реабилитации онкологических пациентов [33].…”
Section: качество жизни онкологических пациентов с кардиоваскулярной ...unclassified
“…Cancer survivors are less likely than the general population to meet the guidelines for physical activity [3]. Increasing older cancer survivors' physical activity levels is a priority due to the potential to reduce their risk for comorbidities, improve their quality of life and even increase their longevity [4,5]. Interventions to increase physical activity among cancer survivors show promise as well as challenges to maintaining behavior change [6,7].…”
Section: Introductionmentioning
confidence: 99%